Non-weighted l2/L2-gain of asynchronously switched systems. (December 2021) - Liu, Yang; Chen, Xiaoying; Lu, Jianquan; Gui, Weihua
Abstract: This paper concerns that a non-weighted l 2 / L 2 -gain performance for asynchronously switched systems can be achieved in both discrete-time and continuous-time cases. Based on the constructed Lyapunov-like functions with average dwell time (ADT) method and inequality analysis technique, a non-weighted l 2 / L 2 -gain for asynchronously switched nonlinear systems can be guaranteed, which improves the existing results. Meanwhile, for asynchronously switched linear systems, the piecewise Lyapunov matrices are constructed and linear matrix inequalities (LMIs) conditions are derived to attain a non-weighted l 2 / L 2 -gain performance. Finally, some examples are provided to illustrate the theoretical results.